Implementation Independent Curriculum in Increase 21st Century Competencies of Students Elementary school - Risma Hartati; Elisabeth Ruthana Lasmaria Sinaga; Enjel Monica Br Sinulingga; Jenwi Nonita Br Tarigan (CV Putra Publisher, 2026)
This research is motivated by the demands of 21st-century education, which requires students to possess various essential skills, such as critical thinking, creativity, communication, and collaboration (4Cs). However, in reality, the learning process in elementary schools still tends to be teacher-centered, thus not being able to fully develop these competencies optimally. Therefore, the presence of the Independent Curriculum is a strategic effort to encourage more flexible, student-centered, and contextual learning according to student needs. The purpose of this study is to determine how the implementation of the Independent Curriculum improves the 21st-century competencies of elementary school students and to identify supporting and inhibiting factors in its implementation. This study uses a qualitative approach with a descriptive type. The research subjects included teachers and students in elementary schools that have implemented the Independent Curriculum. Data collection techniques were carried out through observation of learning activities, in-depth interviews with teachers, and documentation studies of learning materials. Data analysis was carried out interactively through the stages of data reduction, data presentation, and drawing conclusions. The results show that the implementation of the Independent Curriculum has a significant impact on improving students' 21st-century competencies. In the learning process, teachers have begun to implement various innovative learning models such as Project-Based Learning (PjBL), problem-based learning, and differentiated learning tailored to student characteristics. This encourages students to be more active, independent, and directly involved in the learning process. Students demonstrate improvements in critical thinking skills through problem-solving activities, increased creativity through learning projects, communication skills through presentations of work results, and collaboration skills through group work. In addition, the Independent Curriculum also provides space for teachers to integrate real-life contexts and the surrounding environment into learning, so that learning becomes more meaningful and relevant for students. Implementation. The Pancasila Student Profile also helps strengthen the formation of student character that aligns with 21st-century competencies. However, this study also found several obstacles in the implementation of the Independent Curriculum, including teachers' limited understanding in designing and implementing project-based learning, limited supporting facilities and infrastructure, and the persistence of students who are not accustomed to learning patterns that require activeness and independence. In addition, the administrative burden on teachers and limited training are also inhibiting factors in optimizing the implementation of this curriculum. Based on the research results, it can be concluded that the implementation of the Merdeka Curriculum is effective in improving 21st-century competencies in elementary school students, particularly in critical thinking, creativity, communication, and collaboration. To support optimal success, teacher competency improvement is needed through ongoing training, adequate facilities and infrastructure, and support from various parties